2007
DOI: 10.1111/j.1944-9720.2007.tb02868.x
|View full text |Cite
|
Sign up to set email alerts
|

Language Learning Strategy Use: Perceptions of Female Arab English Majors

Abstract: This study investigated the patterns of language learning strategy use among 120 female Arabic‐speaking students majoring in English at a university in Qatar. Perceptions of strategy use were measured by the Strategy Inventory for Language Learning (SILL, ESL/EFL Student Version). The study found that (1) this group of EFL learners featured medium bordering on high strategy users with an overall mean of 3A6 out of 5; (2) strategy categories were used in the order of metacognitive, cognitive, compensation, soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
46
3
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(81 citation statements)
references
References 11 publications
26
46
3
6
Order By: Relevance
“…The higher the mean score, the higher would be the tendency for the respondents to use the strategy. Studies conducted in other university contexts (Goh and Kwah, 1997;Bremner, 1999;Klassen, 1994;Yang, 1994;Abdolmehdi Riazi, 2007) generally show results consistent with the present study in so far as the compensation and memory strategies are concerned. Goh and Kwah's (1997) survey on the strategy use of tertiary-level students from the People's Republic of China (PRC) learning English as a Second Language in Singapore, reported metacognitive and compensation strategies to be the most frequently used, whereas memory strategies the least used.…”
Section: Research Question 4: Are There Differences In Learning Stratsupporting
confidence: 79%
See 2 more Smart Citations
“…The higher the mean score, the higher would be the tendency for the respondents to use the strategy. Studies conducted in other university contexts (Goh and Kwah, 1997;Bremner, 1999;Klassen, 1994;Yang, 1994;Abdolmehdi Riazi, 2007) generally show results consistent with the present study in so far as the compensation and memory strategies are concerned. Goh and Kwah's (1997) survey on the strategy use of tertiary-level students from the People's Republic of China (PRC) learning English as a Second Language in Singapore, reported metacognitive and compensation strategies to be the most frequently used, whereas memory strategies the least used.…”
Section: Research Question 4: Are There Differences In Learning Stratsupporting
confidence: 79%
“…As students are responsible for their own learning, looking at the strategies they adopt in language learning could give insights into the importance of the different strategies used, the extent to which they are used, and the factors that influence strategy use. This interest in LLS is evident based on a good number of valuable research on LLS in the different English as a Second Language (ESL) and English as a Foreign Language (EFL) contexts (e.g., Abdolmehdi Riazi, 2007;Kamarul Shukri Mat Teh, Mohamed Amin Embi, Nik Mohd Rahimi Nik Yusoff & Zamri Mahamod, 2009;Abu Shmais, 2003;Li, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Khalil (2005), the university students' results showed that their language proficiency level had an effect on five language learning strategy categories and the results favoured female students over males in 16 individual strategies. In another study conducted on Arabic L1 speakers by Riazi (2007) who investigated the patterns of language learning strategy use of 120 female Arabic-speaking students who were majoring in English at a university in Qatar. The participants were of average proficiency level, and were from all educational levels in the university.…”
Section: Language Learning Strategiesmentioning
confidence: 99%
“…Many studies have been conducted to establish the relationship between ESL/EFL learning strategies, and the wide range of variables found in learners such as age or school year (e.g., Griffiths, 2003;Oxford & Ehrman, 1995;Riazi, 2007;Srisupha, 2012), English proficiency (e.g., Baker & Boonkit, 2004;Ghafournia, 2014;Murray, 2010), cultural background (e.g., Alhaisoni, 2012;Lengkanawati, 2004), motivation (e.g., Oxford & Nyikos, 1989), and personality traits (e.g., Kaufman et al, 2008;Moldasheva & Mahmood, 2014). Previous studies also found that more successful ESL/EFL learners tend to make more frequent use of learning strategies overall (e.g., Ghani, Mahfuz, Saad, & Yusoff, 2014;Akbari, 2003, Green & Oxford, 1995Murray, 2010;Wharton, 2000).…”
Section: Learning Strategy and Language Proficiencymentioning
confidence: 99%